Investigation of trial registration as part of a research integrity assessment of randomised controlled trials in COVID-19 evidence syntheses: a meta-epidemiological study - Patrick Meybohm; Stephanie Weibel; Emma Sydenham; Florencia Weber; Tamara Pscheidl (BMJ Open)
Objectives Prospective registration of randomised controlled trials (RCTs) is an international standard of good clinical practice but is often neglected by evidence synthesis producers. This study aims to assess prospective registration of RCTs included in evidence syntheses as part of a research integrity assessment and examine its impact on the study pool.Design Meta-epidemiological study.Data sources COVID-19 Cochrane reviews (CRs) and non-Cochrane systematic reviews (SRs) in MEDLINE via PubMed up to 9 June 2022.Eligibility criteria RCTs from CRs and SRs evaluating 13 investigational medicinal products for SARS-CoV-2 and COVID-19.Data extraction and synthesis We assessed prospective trial registration in RCTs according to domain 2 of the research integrity assessment tool. Prospective registration is defined as registration before participant enrolment. We extracted the trial registration number, registration date, study start date and inconsistencies in dates between study report and registration. RCTs were categorised as ‘no concern’, ‘awaiting classification’ and ‘exclude’. We also analysed the relationship between study settings, publishing journals and prospective registration.Results We included 188 RCTs. In the primary study report, 91% reported a trial registration number. In 84 RCTs, either not or retrospectively registered or with missing or inconsistent dates, we searched and/or contacted study authors for prospective registrations, resolving 17 RCTs. Ultimately, 58% of RCTs were prospectively registered and considered ‘no concern’, 15% were ‘awaiting classification’ due to inconsistent or missing information and 27% were either not registered or retrospectively registered and categorised as ‘exclude’. Prospective registration was higher in larger or international multicentre RCTs and in RCTs conducted in Europe.Conclusions If prospective trial registration is required for inclusion in evidence syntheses, only 6 out of 10 COVID-19 RCTs would be eligible. Restricting eligibility to prospectively registered RCTs would include most large and international multicentre RCTs but exclude many smaller and non-European RCTs.Protocol registration The protocol is available on OSF (https://osf.io/3bzeg).